Predicting Marital Conflicts in Couples Based on A Systemic Approach Mediated by Personality Traits - Dousti, Fatemeh; Mirzahosseini , Hassan; Zargham Hajebi, Majid (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Marital conflicts are among the main factors that threaten marital relations and contribute to conflicts and divorces in Iranian society. The present study has been carried out in order to predict marital conflicts in couples based on a systemic approach mediated by personality traits in the cities of Tehran and Qom. Methods: The research method was descriptive-correlational. The statistical population consisted of troubled/struggling couples in Tehran and Qom. The sample consisted of 540 men and women with marital conflict selected by convenience sampling. The research instruments included Neuroticism, Extraversion, Openness, Agreeableness, and Conscientiousness, (NEO) Five-Factor Inventory (NEO-FFI), Marital Conflict Questionnaire (MCQ), and the Family Assessment Device (FAD). Data were analyzed by Pearson correlation method and structural equation modeling using SPSS version 22.0 and LISREL version 8.0 software. Results: Results revealed that the hypothetical model fit the measurement model (CFI = 0.97; IFI = 0.96; RMSEA = 0.088). In addition, the systemic approach components mediated by personality traits were able to explain marital conflicts (P = 0.001). These components indirectly influenced marital conflicts through personality traits (β = -0.38, P = 0.005). Conclusions: Overall, the findings verified the marital conflict model based on a systemic approach mediated by the personality traits.